2005
DOI: 10.1007/s00267-004-0171-1
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of Soil Polluted by Nickel Using Agricultural Crops

Abstract: Soil pollution due to heavy metals is widespread; on the world scale, it involves about 235 million hectares. The objectives of this research were to establish the uptake efficiency of nickel by some agricultural crops. In addition, we wanted to establish also in which part of plants the metal is stored for an eventual use of biomass or for recycling the metal. The experiments included seven herbaceous crops such as: barley (Hordeum vulgaris), cabbage (Brassica juncea), spinach (Spinacea oleracea), sorghum (So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(30 citation statements)
references
References 5 publications
1
28
0
1
Order By: Relevance
“…In their research on various crops abilities for nickel accumulation, Giordani et al (2005) indicated a higher potential of spinach for this metal uptake (65 g Ni ton -1 ) in comparison with cabbage, barley, sorghum or beans. In authors' own research, field bean and lettuce revealed almost twice higher efficiency in nickel removal in comparison with maize.…”
Section: Discussionmentioning
confidence: 99%
“…In their research on various crops abilities for nickel accumulation, Giordani et al (2005) indicated a higher potential of spinach for this metal uptake (65 g Ni ton -1 ) in comparison with cabbage, barley, sorghum or beans. In authors' own research, field bean and lettuce revealed almost twice higher efficiency in nickel removal in comparison with maize.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the toxicity effect on plants, such as growth reduction, is not observed when citric acid is applied, in contrast to EDTA (Evangelou et al, 2006). The excellent reports from do Nascimento et al (2006a) and Freitas et al (2009) showed the efficiency of the application of organic acids as phytoextraction assistants for a wide range of heavy metals, recomPlant species such as sunflower (Helianthus annuus L.), jack bean (Canavalia ensiformis L.), velvet bean (Stizolobium aterrimum L.), castor bean (Ricinus communis L.) and others have been extensively exploited for their heavy metal tolerance and phytoremediation potential (Adhikari and Kumar, 2012;de Andrade et al, 2005;de Andrade et al, 2008;de Souza et al, 2011;Giordani et al, 2005;Ullah et al, 2011). Studies with these plant species have been carried out in hydroponic systems under greenhouse conditions to better understand the patterns of response, distribution and accumulation of heavy metals.…”
Section: Organic Chelating Agentsmentioning
confidence: 99%
“…Brassicas olaracea (kale) has very high hyperaccumulation and tolerance for Ni (Giordani, Cecchi, & Zanchi, 2005;Kabata-Pendias & Mukherjee, 2007). Based on the nitrate levels in sampled kale, it was estimated that 0.381.32 mg nitrates were consumed daily based on the consumption of 7 ounces (200 g) of kale as estimated by Onyango (2008) (figure 7).…”
Section: ) Various Studies Have Demonstrated Thatmentioning
confidence: 99%